Philippine encyclopedia of the social sciences - Salita, Domingo C.; Philippine Social Science Council (Quezon City Philippine Social Science Council, 1993)
For the promotion of education, the Philippine Encyclopedia of the Social Sciences is published consisting of five volumes arranged by discipline. Due to some circumstances, the general reference section only acquires two volumes covering the discipline of history which attempts to give a portrayal of the state of the art social sciences in the Philippines today. Volume I discusses the definition and characteristic while Volume II presents the development and advancement of history and historians.
"This encyclopedia was conceived to meet the needs of the high school and college students as well as the general public for a ready reference in the field of the social sciences that are oriented to local conditions. The topics in the encyclopedia are arranged by discipline. It has a wealth of information on discipline like anthropology, communication, demography, economics, geography, history, linguistics, political science, psychology, public administration, social work, sociology and statistics. It has maps and illustrations to facilitate understanding of the contents." cross references and index are also included.
Fi-12543, Fi-12544, Fi-12546 donated by Prof. Mamoru Tsuda, M.A., U.P.
Keywords: Social sciences -- Philippines -- Encyclopedias